Fracture behavior of PH15-5 stainless steel manufactured via directed energy deposition - Huang, Sheng (2024)
The tensile properties, fracture toughness, and fatigue crack growth (FCG) characteristics of a directed energy deposited precipitation hardened stainless steel (grade: PH15-5; age hardening heat treatment condition: H900) were examined. In the as-fabricated condition, the alloy contains microfissures that are oriented parallel to the build direction, whose appearance was difficult to be detected using optical microscopy. Due to their relative orientation w.r.t. the loading direction, significant anisotropy in tensile and FCG behavior was noted, with the properties being particularly lower when the loading direction is perpendicular to the crack orientation. Despite the presence of microfissures, the alloy's fracture initiation toughness is comparable to (or in some cases exceeds) those manufactured using either conventionally techniques or laser powder bed fusion. Activation of the extrinsic toughening mechanisms, such as crack deflection when its mode I direction is perpendicular to the microfissures and a combination of crack bridging and deflection when it is parallel, are the micromechanical reasons for the observed high toughness. The efficacy of such mechanisms is observed to depend on the plastic zone size relative to the microfissure spacing. The understanding developed in this study enables the development of strategies for enhancing the damage tolerance of additively manufactured alloys.